Beiträge zur Insekten-Fauna der DDR: Lepidoptera - Epermeniidae. - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The present paper deals with the eight species of Epermeniidae found in the GDR. Three other species are included because their occurrence can be assumed. A key facilitates the determination of these eleven species.